Digital Economy in Industrial 4.0 - R R Oktaviana; Tatik Fidowaty (Peneliti.net, 2021)
The purpose of this study is to find out the economic development in Indonesia which has developed towards a promising digital economy on industrial 4.0. The presence of a digital economy and easy access to the internet has increased people's interest to shop online. This research used a descriptive method, which collects research data by surveys, observations, and interviews several respondents related to this research. The results of this research show the conclusion on economic growth that influenced by the consumptive behavior of Indonesian people in online buying and selling transactions as well as factors that influence the progress of e-commerce in the industrial revolution 4.0. Hence, e-commerce in Indonesia has good potential for economic growth such as small businesses in Indonesia.